2017
DOI: 10.1007/s00705-017-3480-4
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence and phylogenetic analysis of Senecavirus A isolated in Northeast China in 2016

Abstract: Senecavirus A (SVA) is associated with vesicular disease in swine and the acute death of neonatal piglets. Here, senecavirus A was isolated from a pig displaying vesicular disease in Northeast China. The virus was designated as SVA/HLJ/CHA/2016 and its full-length nucleotide sequence was determined and analyzed in comparison with other known SVA strains. The complete genome sequence of SVA/HLJ/CHA/2016 shares high nucleotide identities, of 93.8 to 99%, with previously reported SVA full-length genomes. Phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Foreign animal disease investigations indicated that other vesicular viral pathogens, such as foot-and-mouth disease virus (FMDV), swine vesicular disease virus (SVDV), vesicular stomatitis virus (VSV), and vesicular exanthema of swine virus (VESV), were negative in these cases [10]. Subsequently, SVV detection was reported by other laboratories in the U.S. [11][12][13][14][15][16], China [17][18][19][20][21], Canada [22], Thailand [23], and Colombia [24]. Vesicular lesions were induced in pigs following experimental inoculation with the contemporary U.S. isolates of SVV [25,26], confirming that SVV is a vesicular viral pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Foreign animal disease investigations indicated that other vesicular viral pathogens, such as foot-and-mouth disease virus (FMDV), swine vesicular disease virus (SVDV), vesicular stomatitis virus (VSV), and vesicular exanthema of swine virus (VESV), were negative in these cases [10]. Subsequently, SVV detection was reported by other laboratories in the U.S. [11][12][13][14][15][16], China [17][18][19][20][21], Canada [22], Thailand [23], and Colombia [24]. Vesicular lesions were induced in pigs following experimental inoculation with the contemporary U.S. isolates of SVV [25,26], confirming that SVV is a vesicular viral pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…From 2015 to January 2016, the PIVD outbreak was still observed in swine herds in Guangdong province (Zhao et al., ). PIVD began to appear in Hubei and Heilongjiang provinces in 2016 (Qian, Fan, Qian, Chen, & Li, ; Wang et al., ). In January 2017, PIVD outbreaks were noted in Fujian and Henan provinces (Zhu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In China, the first SVA infection was reported in 2015 in Guangdong Province (12). Since then, other cases have been sporadically reported in several regions with a significant increase in numbers and geographical distributions (15,16,18). The high density of pig farms and frequent movement of live pigs through different regions will contribute to the SVA spread in China.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, increasing cases of SVA infection have been reported in other provinces, including Heilongjiang, Hubei, Henan, Fujian, Hebei, and Anhui etc. (13)(14)(15)(16)(17)(18). However, the genomic information is still very limited in these regions except Guangdong province which account for over 70% of Chinese isolates (19).…”
Section: Introductionmentioning
confidence: 99%